Answer:
D. c(p) = 0.42p
Explanation:
total cost = .42(P)
Example: 5 lbs
$2.10 = $.42(5)
c(p) = 0.42p <== ur function
Since a pound of sugar increases proportionally to the total cost of sugar bought, then the function can be written as:
c(p) = 0.42p
Where: c(p) = total cost of sugar bought
p = pounds of sugar
c(p) is a function of p, because c(p) depends on p.
Answer: The function rule that gives the total cost is given by
Explanation:
Let the number of pounds of sugar be 'p'.
Let the total cost would be C(p).
Cost of each pound = $0.42
So, the function rule would be
Hence, the function rule that gives the total cost is given by